Knots and colorability - Azram, Mohammad (INSInet Publications, 2012)
We have established that tricolourability would be a way of distinguishing some of knots(links) by showing that tricolorability is an ambient isotopy invariant. We have extended the notion of tricolorability to colorability of knot(link) and have shown that colorability of knot (link) is also an ambient isotopy invariant. We have shown that no knot is colorable mod 2 but instead every link with more than one component is colorable mod 2. We have also established that bridge number of a knot is always one.